Diplomasi Ekonomi Indonesia: Hongaria sebagai Pintu Gerbang Pasar Prospektif di Eropa Tengah dan Timur - Reskiyah, Emy Sri (Jurnal Ilmiah Hubungan Internasional Fajar, 2022)
Indonesia and Hungary have long established good relations, which is reflected in economic relations, including trade, investment, and tourism. These sectors’ performance is a very important indicator for measuring the success of Indonesia's economic diplomacy with Hungary. This study uses descriptive statistical analysis quantitative methods concerning the bilateral relationship between Indonesia and Hungary in the field of economic cooperation and is followed by an analysis of strengths, weaknesses, opportunities, and threats (SWOT). This paper aims to examine the bilateral relations that exist between Indonesia and Hungary in the field of economic cooperation, especially but not limited to the trade, investment, and tourism sectors as part of economic diplomacy in the last ten years (2013- 2022). The result of this study shows Hungary has the potential as a gateway as well as a new prospective market for Indonesia. To make Hungary a gateway for Indonesia's economic diplomacy in the Central and Eastern European Region, collaboration from the penta helix or multi-stakeholders is needed including the government, business people/practitioners, academics, communities, and the media. Keywords: Economic Diplomacy; Trade; Investment; Tourism; Prospective Market